Disturbing pleasures: learning popular culture - Giroux, Henry (New York: Routttedge, 1994)
Contents: dsiney, bretton and beyond. 1. consuming social change: the united colors of benetton. 2. politics and innocence in the wowonderfull of disney. 3. school for scandall: whittling away at public education. 4. write utopias and nightmare realities. film and the new cultural racism. pedagogy and the cutical practice of photography. cultural studies does anybody write in the cultural satudies classhitellectual. traveling pedagogics
Keywords: Popular Culture - United States